FORMATION OF NEW EXPERIENCE IN ORGANISING COMMUNICATION INTERACTION TO ENSURE THE GOALS OF SUSTAINABLE DEVELOPMENT - Haliuk, I. B.; Haliuk, T. S.; Haliuk, O. S. (The actual problems of regional economy development, 2023)
The article is concerned with defining the role of organisational communications for achieving the goals of sustainable development of an enterprise and the specifics of communication interaction in the context of changes. To achieve the goal of the study, the authors used the method of theoretical research, general logical and generalisation methods. The authors consider the concept of sustainable development, which involves the integration of social, economic and environmental aspects into the business strategy of an enterprise. It is noted that in a period of change, sustainable development of an enterprise implies the ability to adapt to changes and adapt its strategy to new conditions. The article presents the components of the study of communication and sustainable development, which include: the relationship between communication in the enterprise and sustainable development; perception of sustainable development strategies by employees; interaction between employees and management; the relationship between communication in the enterprise and sustainable financial success; development and implementation of communication strategies to achieve sustainable development. It is noted that effective communication is aimed at building trusting relationships and increasing employee loyalty to their company. In the course of the study, the specifics of organisational communications in the context of changes are highlighted, the latter including the pandemic and martial law in Ukraine. It is determined that during the period of quarantine restrictions, the usual methods of communication became ineffective. The situation required a change in the format of communications and the active development of digitalisation of activities, which allowed for the sustainable development of enterprises at a different level of interaction with employees and target groups. The emotional component became a characteristic feature of wartime communications, which resulted in the formation of the main trends in wartime communications: the value trend, the support trend and the national trend. It has been determined that communication interaction at the enterprise level has changed vectors in the direction of increasing communication with employees, providing them with current information and forecasts of work in the near future. On the basis of the study, the authors draw conclusions, the main of which is that during martial law a new value-based approach to organisational communications was formed, which allows, through the development of corporate culture at a qualitatively higher level, to ensure the dynamic development of the enterprise and achievement of sustainable development goals in the future.